How an Interdisciplinary Approach to Narrative Can Support Policymaking on Migration and Integration at the City Level. Issue 1 (September 2021) - Broadhead, Jacqueline
Narrative change and strategic communications are attractive tools for city officials setting policy for integration and migration. These tools allow for the construction and development of shared stories of place-based identity and belonging. Stories about migration often focus on (border) control, the value of the contribution of migrants, and the need for compassion. However, these frames of compassion and control are often oppositional: they can alienate rather than persuade, and they can neglect constituents whose views do not align with the polarities. They also elide other narrative frames, which may appeal to broader groups, particularly those focused on integration and belonging. This article analyzes three cities' attempts at narrative change strategies that complexify migration narratives with place-based narratives of inclusion. From these case studies, this article identifies practical implications for local policy-makers and sets an interdisciplinary agenda for future research.